Smashing grammar : a guide to improving your writing skills and avoiding common mistakes - Shrives, Craig (London : Kyle Books, 2019)
Have you ever sent an email and then realised you've used the wrong kind of your? Do you hope for the best when writing loose or lose? Are semicolons a mystery to you? Armed with Smashing Grammar, you will be able to boost your confidence, sharpen your writing skills and refine your vocabulary without breaking a sweat. Easy to navigate and packed with real-life examples, this helpful and friendly guide includes a comprehensive checklist of common pitfalls and mistakes to avoid, from knowing when to use a possessive apostrophe correctly to mastering there and their.
Keywords: English language -- Grammar